Konseling Multidimensional untuk Mengatasi Permasalahan Emosional Siswa SMP IT - Wirawn, Pandy Akbar; Fadila, Fadila; Rizal, Syamsul; Azwar, Beni; Hartini, Hartini; Rosyidah, Isy Maryam (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to examine the implementation of a multidimensional counseling approach in addressing emotional problems among students at Rabbi Radhiyya Integrated Islamic Junior High School (SMP IT). This approach views the individual holistically through five dimensions: cognitive, affective, behavioral, social, and spiritual. The method used was a qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation of students experiencing emotional symptoms such as academic anxiety, low self-esteem, aggressiveness, loss of enthusiasm for learning, and difficulties in social adaptation. The results showed that this approach was able to help students recognize and manage their emotions, improve social interactions, and strengthen Islamic values. The implementation of multidimensional counseling has proven effective in reducing emotional symptoms and supporting the development of students' overall character. This approach is relevant for application in Islamic educational environments because it is curative, preventative, and transformative.